Screening for Small Molecule Inhibitors of Statin-Induced APP C-terminal Toxic Fragment Production - Poksay, Karen S.; Sheffler, Douglas J.; Spilman, Patricia; Campagna, Jesus; Jagodzinska, Barbara; Descamps, Olivier; Gorostiza, Olivia; Matalis, Alex; Mullenix, Michael; Bredesen, Dale E.; Cosford, Nicholas D. P.; John, Varghese (Frontiers in Pharmacology, 2017)
Alzheimer’s Disease (AD) is characterized by neuronal and synaptic loss. One process that could contribute to this loss is the intracellular caspase cleavage of the amyloid precursor protein (APP) resulting in release of the toxic C-terminal 31-amino acid peptide APP-C31 along with the production of APPC31, full-length APP minus the C-terminal 31 amino acids. We previously found that a mutation in APP that prevents this caspase cleavage ameliorated synaptic loss and cognitive impairment in a murine AD model. Thus, inhibition of this cleavage is a reasonable target for new therapeutic development. In order to identify small molecules that inhibit the generation of APP-C31, we first used an APPC31 cleavage site-specific antibody to develop an AlphaLISA to screen several chemical compound libraries for the level of N-terminal fragment production. This antibody was also used to develop an ELISA for validation studies. In both high throughput screening (HTS) and validation testing, the ability of compounds to inhibit simvastatin- (HTS) or cerivastatin- (validation studies) induced caspase cleavage at the APP-D720 cleavage site was determined in Chinese hamster ovary (CHO) cells stably transfected with wildtype human APP (CHO-7W). Several compounds, as well as control pan-caspase inhibitor Q-VD-OPh, inhibited APPC31 production (measured fragment) and rescued cell death in a dose-dependent manner. The effective compounds fell into several classes including SERCA inhibitors, inhibitors of Wnt signaling, and calcium channel antagonists. Studies are underway to evaluate the efficacy of lead compounds revealed here in mouse models of AD, as well as to identify additional compounds and determine the mechanisms by which they exert their effects.